Influence of Integrated Soil fertility Management on the Vegetative Growth Parameters of Zea mays in the Guinea Savanna Eco-Zone of Ghana - Abukari, Ammal (Journal of Agricultural Sciences (Belgrade), 2020)
All over the world attention has been drawn to the use of eco-friendly biochar application to improve on crop productivity. In Ghana, there are available potential feedstocks left unused and can be used for the production of biochar. Therefore this study investigated the effect of different rates of rice husk biochar and different rates of inorganic nitrogen (N) for optimum growth of Zea mays in Nyankpala, Northern Ghana. Field experiments were conducted in the cropping period of 2012. The treatments involved 4 different rate of application of inorganic nitrogen fertilizer (0 kg N/ha, 30N/ha, 60 kg N/ha and 90 kg N/ha) and different rates of rice husk biochar (0t/ha, 2t/ha and 4t/ha). The treatments were allocated in a split plot design with three replications. The vegetative parameters assessed were number of leaves, plant height and plant girth. Treatments showed significant (p<0.05) influence on all the traits considered. The combined effects of inorganic nitrogen fertilizer and rice husk biochar significantly influenced the vegetative growth parameters of Zea mays with the maximum values recorded at 4ton/ha rice husk biochar. Yet, this observation in performance is in par with 2ton/ha rice husk biochar which recorded optimum growth parameters compared to the control. It was concluded within the limit of this work that growth parameters of Zea mays in the guinea savanna eco-zone of Ghana could significantly be improved by applying of 4ton/ha rice husk biochar. Integrated soil fertility management (ISFM), a prudent combination of inorganic fertilizers and residues from various sources to sustain the environment is currently a necessity. The experiment revealed that application of rice husk biochar can improve the growth parameters of Zea mays. Yet, further experiments need to be done using higher rates of rice husk biochar to ensure the appropriate rate of biochar application.